Looking at Employee Interpersonal Communication - Chamid, Abdul (LPPPIPublishing, 2024)
This study aims to determine the importance of interpersonal communication in increasing customer satisfaction at Edmond Auto Garage. This research uses a descriptive approach with a qualitative research type. Data were collected through interviews, observation, and recording. Five customers were selected as informants in this study. The results showed that interpersonal communication from the components of openness, empathy, supportiveness and positiveness was successful and met the client's expectations. Therefore, good interpersonal communication can be a supporting factor for customer satisfaction.